Clinico- radiological profile of genetically proven Complicated Hereditary Spastic Paraparesis: A case series - Ranjan, Abhay; Kumar, Abhishek; Sinha, Neetu; Mudassir, Sanaullah (Nepal Journal of Neuroscience, 2022)
Complicated Hereditary Spastic Paraparesis (HSP) is a group of heterogenous neurodegenerative disease characterized by progressive spastic paraparesis with additional features like cognitive impairment, seizures, movement disorders, visual loss, deafness, peripheral neuropathy, and pes cavus. There have been few case series reported in literature from India. We herein report four cases of complicated HSP. Four (three females and 1 male) patients of genetically confirmed HSP with a mean age of onset 10.5 years were recruited. There was mean delay of 8 years in reaching diagnosis. MRI brain showed thinning of corpus callosum in three patients and Ear of lynx sign in two patients. Next Generation Clinical Exome Sequencing confirmed mutations in SPG11 gene in three patients and SLC2A1 in one patient. SPG11 gene mutations were the most frequent genetic abnormality with SLC2A1 gene mutation in single patient. Genetically confirmed diagnosis helps in prognostication and genetic counselling.